Damage index of reinforced concrete members based on the energy dissipation capability degradation. (2nd December 2019) - Wang, Yukui; Liu, Zhefeng; Yang, Weijun; Hu, Yi; Chen, Yuping
Summary: Based on the estimation method of the energy dissipation capacity of reinforced concrete members under variable amplitude displacement cycles, the damage quantitative index of reinforced concrete members based on the energy dissipation capacity degradation is proposed. This index can establish a quantitative relationship with the energy dissipation capacity requirements and material parameters (yield force, yield displacement, and stirrup ratio). To understand the performance classification criteria of reinforced concrete members under variable amplitude displacement cycles based on the damage quantitative index, nine reinforced concrete members with different reinforcement conditions were tested. It was found that the reinforced concrete members can be classified as undergoing no damage (0 < D k ≤ 0.3), mild damage (0.3 < D k ≤ 0.6), moderate damage (0.6 < D k ≤ 0.7), severe damage (0.7 < D k ≤ 0.8), and destruction (0.8 < D k ≤ 1), where the five performance states are based on the damage quantitative index. The performance classification criteria were verified by 18 flexural failure specimens in the Pacific Earthquake Engineering Research Center database.